Advances in Hydrogen Production from Natural Gas Reforming. Issue 11 (6th July 2021) - Boretti, Alberto; Banik, Bimal K.
Abstract : Steam natural gas reforming is the preferred technique presently used to produce hydrogen. Proposed in 1932, the technique is very well established but still subjected to perfections. Herein, first, the improvements being sought in catalysts and processes are reviewed, and then the advantage of replacing the energy supply from burning fuels with concentrated solar energy is discussed. It is especially this advance that may drastically reduce the economic and environmental cost of hydrogen production. Steam reforming can be easily integrated into concentrated solar with thermal storage for continuous hydrogen production. Abstract : Steam methane reforming (SMR) is the favored technique to produce hydrogen, well established but subjected to perfections in catalysts and processes. Herein, the decomposition of CH4 in the presence of Ni on TiO2 support is shown. Especially replacing energy supply from burning fuels with concentrated solar energy is avenue to drastically reduce economic and environmental cost of hydrogen production by SMR.